Superconvergence of Rectangular Mixed Finite Element Methods for Constrained Optimal Control Problem (Advances in Applied Mathematics and Mechanics, 2010)
We investigate the superconvergence properties of theconstrained quadratic elliptic optimal control problem which issolved by using rectangular mixed finite element methods. We use thelowest order Raviart-Thomas mixed finite element spaces toapproximate the state and co-state variables and use piecewiseconstant functions to approximate the control variable. We obtainthe superconvergence of $\mathcal{O}(h^{1+s})$ $(0$